Correlación de hallazgos histopatológicos e imagenológicos de la distorsión de arquitectura mamaria detectada en mamografía digital con tomosíntesis - Vargas Desposorio, Yuri Yessenia (2020)
Breast cancer is the second most common in women worldwide, reporting an increasing incidence in developing countries. Fortunately, its early detection through routine screening with digital mammography has been shown to decrease morbidity and mortality. For many years, 2D mammography was the main tool in the search for lesions suspected of malignancy. Nowadays, tomosynthesis allows the detection of subtle lesions that may be occult on 2D mammography, which improves the detection of breast cancer. Architectural distortion (AD) is one of these lesions and represents the third most frequent mammographic appearance of non-palpable cancer. Although its presence makes it necessary to rule out a neoproliferative etiology, in some cases it could be benign. The purpose of this retrospective study is to determine if there is an adequate correlation between architectural distortion detected in mammography with tomosynthesis and histopathologic outcomes, as well as to identify their imaging characteristics. 83 cases of architectural distortion diagnosed between January 1, 2018 and December 31, 2019 were studied. Mammographic characteristics of AD, ultrasound findings, and histopathologic outcomes were recorded for subsequent analysis using the Chi 2 test.